Meta-analysis of RCTs finds that increasing consumption of polyunsaturated fat as a replacement for saturated fat reduces the risk of coronary heart disease. Issue 4 (3rd August 2010) - Hooper, Lee
Abstract : Commentary on: Mozaffarian D Micha R Wallace S . Effects on coronary heart disease of increasing polyunsaturated fat in place of saturated fat: a systematic review and meta-analysis of randomized controlled trials . PLoS Med 2010 ;7 :e1000252 .